Research developments in computer vision and image processing: Methodologies and applications - Srivastava R.; Singh S.K.; Shukla K.K. (My University, 2025)
Similar to the way in which computer vision and computer graphics act as the dual fields that connect image processing in modern computer science, the field of image processing can be considered a crucial middle road between the vision and graphics fields. Research Developments in Computer Vision and Image Processing: Methodologies and Applications brings together various research methodologies and trends in emerging areas of application of computer vision and image processing. This book is useful for students, researchers, scientists, and engineers interested in the research developments of this rapidly growing field. © 2014 by IGI Global. All rights reserved.